Inhibition of l-type amino acid transporter 1 activity as a new therapeutic target for cholangiocarcinoma treatment. Issue 3 (February 2017) - Yothaisong, Supak; Dokduang, Hasaya; Anzai, Naohiko; Hayashi, Keitaro; Namwat, Nisana; Yongvanit, Puangrat; Sangkhamanon, Sakkarn; Jutabha, Promsuk; Endou, Hitoshi; Loilome, Watcharin
Unlike normal cells, cancer cells undergo unlimited growth and multiplication, causing them to require massive amounts of amino acid to support their continuous metabolism. Among the amino acid transporters expressed on the plasma membrane, l- type amino acid transporter-1, a Na + - independent neutral amino acid transporter, is highly expressed in many types of human cancer including cholangiocarcinoma. Our previous study reported thatl -type amino acid transporter-1 and its co-functional protein CD98 were highly expressed and implicated in cholangiocarcinoma progression and carcinogenesis. Therefore, this study determined the effect of JPH203, a selective inhibitor ofl -type amino acid transporter-1 activity, on cholangiocarcinoma cell inhibition both in vitro and in vivo. JPH203 dramatically suppressed [ 14 C]l -leucine uptake as well as cell growth in cholangiocarcinoma cell lines along with altering the expression ofl -type amino acid transporter-1 and CD98 in response to amino acid depletion. We also demonstrated that JPH203 induced both G2/M and G0/G1 cell cycle arrest, as well as reduced the S phase accompanied by altered expression of the proteins in cell cycle progression: cyclin D1, CDK4, and CDK6. There was also cell cycle arrest of the related proteins, P21 and P27, in KKU-055 and KKU-213 cholangiocarcinoma cells. Apoptosis induction, detected by an increase in trypan blue–stained cells along with a cleaved caspase-3/caspase-3 ratio, occurred in JPH203-treated cholangiocarcinoma cells at the highest concentration tested (100 µM). As expected, daily intravenous administration of JPH203 (12.5 and 25 mg/kg) significantly inhibited tumor growth in KKU-213 cholangiocarcinoma cell xenografts in the nude mice model in a dose-dependent manner with no statistically significant change in the animal's body weight and with no differences in the histology and appearance of the internal organs compared with the control group. Our study demonstrates that suppression ofl -type amino acid transporter-1 activity using JPH203 might be used as a new therapeutic strategy for cholangiocarcinoma treatment.